2016
DOI: 10.5194/acp-16-417-2016
|View full text |Cite
|
Sign up to set email alerts
|

Global tropospheric ozone variations from 2003 to 2011 as seen by SCIAMACHY

Abstract: Abstract. An analysis of the tropospheric ozone (O 3 ) columns (TOCs) derived from SCIAMACHY limb-nadirmatching (LNM) observations during the period 2003-2011, focusing on global variations in TOC, is described. The changes are derived using a multivariate linear regression model. TOC shows changes of −0.2±0.4, 0.3±0.4, 0.1±0.5 and 0.1 ± 0.2 % yr −1 , which are not statistically significant at the 2σ level in the latitude bands 30-50 • N, 20 • S-0, 0-20 • N and 50-30 • S, respectively. Tropospheric O 3 shows s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
41
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(45 citation statements)
references
References 143 publications
(196 reference statements)
4
41
0
Order By: Relevance
“…[] and Langford [], which found correlations between free tropospheric ozone and El Niño following a several month (from 2 to 6 months) lag in lidar data from a site in Colorado, as originating from enhanced STE induced by ENSO. Despite the fact that ENSO‐related tropospheric O 3 responses over tropical and extratropical regions have been reported in recent studies [e.g., Oman et al ., ; Lin et al ., ; Neu et al ., ; Ziemke et al ., ; Ebojie et al ., ; Olsen et al ., ], it is the first time that such a timing of the O 3 response is identified from satellite measurements, which constitutes an important finding of this study. Note, finally, that longer time lags for ENSO have been also tested in this study but without significant improvement on the fitting residuals.…”
Section: Patterns Of Geophysical Variables: Results and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[] and Langford [], which found correlations between free tropospheric ozone and El Niño following a several month (from 2 to 6 months) lag in lidar data from a site in Colorado, as originating from enhanced STE induced by ENSO. Despite the fact that ENSO‐related tropospheric O 3 responses over tropical and extratropical regions have been reported in recent studies [e.g., Oman et al ., ; Lin et al ., ; Neu et al ., ; Ziemke et al ., ; Ebojie et al ., ; Olsen et al ., ], it is the first time that such a timing of the O 3 response is identified from satellite measurements, which constitutes an important finding of this study. Note, finally, that longer time lags for ENSO have been also tested in this study but without significant improvement on the fitting residuals.…”
Section: Patterns Of Geophysical Variables: Results and Discussionmentioning
confidence: 99%
“…The ENSO influence on tropospheric O 3 in the extratropics may reflect the O 3 response associated with specific tropospheric and stratospheric pathways which are connected with the ENSO changes in the tropics, which alter the tropospheric circulation and which impact on the O 3 levels over the middle and high latitudes [e.g., Langford , ; Zeng and Pyle , ; Koumoutsaris et al ., ; Oman et al ., ; Lin et al ., ; Neu et al ., ; Ebojie et al ., ]. Butler et al .…”
Section: Patterns Of Geophysical Variables: Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A deeper investigation is needed to understand the contributions of tropospheric column ozone and stratospheric column ozone to total column ozone, especially considering uncertainties carefully, but this is beyond the scope of this work. We note that studies using various data sources show less significant regional increases (and some decreases), with global estimates ranging from 0.2 to 0.7 % per year (∼ 0.6-2 DU per decade) (Cooper et al, 2014;Ebojie et al, 2016;Heue et al, 2016), though these estimates considered different time periods. This suggests a large range of uncertainty, but even the lower end of the estimated increases in tropospheric column ozone are in line with the missing part of the total column ozone change, after considering stratospheric column ozone that we estimate here.…”
Section: Tropospheric Ozone Contribution To Total Column Ozonementioning
confidence: 99%
“…In the midlatitudes, tropospheric ozone sensitivity to ENSO has also been identified, albeit with a weaker sensitivity compared to the tropics. Ebojie et al () showed a response in midlatitude TCO observations from the Scanning Imaging Absorption Spectrometer for Atmospheric Chartography, particularly in the NH where the sensitivity is statistically significant in regions as far poleward as 60°N. Likewise, a midlatitude response is evident in IASI TCO observations, as well (Wespes et al, ).…”
Section: Introductionmentioning
confidence: 94%